2020
DOI: 10.3389/fcvm.2020.00016
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Challenges of Radiation-Associated Cardiovascular Dysfunction (RACVD) in Modern Radiation Oncology: Clinical Practice, Bench Investigation, and Multidisciplinary Care

Abstract: Radiotherapy (RT) is a crucial treatment modality in managing cancer patients. However, irradiation dose sprinkling to tumor-adjacent normal tissues is unavoidable, generating treatment toxicities, such as radiation-associated cardiovascular dysfunction (RACVD), particularly for those patients with combined therapies or pre-existing adverse features/comorbidities. Radiation oncologists implement several efforts to decrease heart dose for reducing the risk of RACVD. Even applying the deep-inspiration breath-hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 186 publications
(175 reference statements)
0
5
0
Order By: Relevance
“…Statins are used to lower lipid levels ( 57 ), and can ameliorate IR-induced inflammation and fibrotic remodeling ( 16 , 58 ). Statins have been found to reverse radiation-induced gene expression disorders such as p53.…”
Section: Strategies To Reduce Radiation Injurymentioning
confidence: 99%
“…Statins are used to lower lipid levels ( 57 ), and can ameliorate IR-induced inflammation and fibrotic remodeling ( 16 , 58 ). Statins have been found to reverse radiation-induced gene expression disorders such as p53.…”
Section: Strategies To Reduce Radiation Injurymentioning
confidence: 99%
“…Cancer patients presenting with clinical HF or IHD during or following cancer treatment need access to medical therapy with standard HF regimens or sometimes transcatheter or open surgical interventions [ 13 ]. Combined management with the control of age-related comorbidities and cardiovascular risk factors (such as hypertension, hypercholesterolemia, and diabetes) is crucial [ 135 ].…”
Section: Prevention and Therapy Of Rihdmentioning
confidence: 99%
“…As previously described, preclinical and clinical studies have identified different manifestations of RIHD in BC. However, in-depth knowledge of the biological mechanisms involved in RIHD is needed [ 113 ] to develop new non-invasive detection methods for diagnosis and follow-up. We need to identify specific biomarkers of RT-induced injury [ 64 ], to implement high-resolution imaging techniques in daily practice [ 114 , 115 , 116 ], and to combine the use of omics data with molecular imaging (single-photon emission computed tomography (SPECT-CT)) or positron emission tomography (PET-CT) for early RHID diagnosis [ 117 , 118 ].…”
Section: Future Directionsmentioning
confidence: 99%